(untitled) (The Pretoria Student Law Review, 2023)
This article explores the relationship between human rights and development and the emergence of a Rights-Based Approach to Development (RBAD). It will give a RBAD more consideration in order to contribute to the conceptual direction of academic discourse, and perhaps even the political direction by proposing solutions to Africa’s socio-economic problems, especially in South Africa, which is facing many developmental challenges. Human rights and development have long been understood as separate terms that were incompatible. Historically, development was only perceived for its role in promotion of economic growth and prosperity of particular countries without any consideration for human development and well-being. However, human rights and development cannot be understood separately. Development and human rights share the same goal, which is to promote the dignity and worth of a human person by creating an environment where people can achieve their full potential. Following the adoption of the UN Charter in 1945, development became a key issue for the United Nations and, for the first time, for the international community. Human development is now central to the realisation of human rights. After many years of debating development and human rights, it was agreed that human rights standards and principles do indeed recognise the link between human rights and development. In the 1990s, a RBAD emerged, transforming the global development order and affirming this relationship.